The sexual dysfunction in women with thyroid disorders: a meta-analysis - Nader Salari; Pegah Heidarian; Framarz Jalili; Fateme Babajani; Shamarina Shohaimi; Maryam Nasirian; Masoud Mohammadi (BMC Endocrine Disorders)
Abstract Background Thyroid disorders are common endocrine conditions impacting multiple organs, including the reproductive system and often lead to sexual dysfunction. These effects can vary by gender; for example, women with hypothyroidism frequently experience reduced libido. Low thyroid hormone levels are also linked to vaginal dryness, causing discomfort, especially during intercourse. This study aims to assess the global prevalence of sexual dysfunction in women with thyroid disorders. Methods Systematic searches were performed across electronic databases, including PubMed, Scopus, Web of Science, Embase, ScienceDirect and Google Scholar, to retrieve studies reporting the prevalence of sexual dysfunction in patients with thyroid disorders up to February 8, 2024. Inclusion criteria comprised studies that reported on the prevalence of female sexual dysfunction (FSD) in patients with thyroid disorders and studies published in English available full text. Exclusion criteria included case studies, intervention studies, studies with incomplete information, repeated studies and those not written in English. Cross-sectional studies were the primary study design included. Data were analyzed using the Comprehensive Meta-Analysis software (Version 2). Results Analysis of nine studies, involving a total sample size of 1013, found an overall prevalence of sexual dysfunction in women with thyroid disorders to be 44.8% (95% CI: 33.8–56.2). Given the substantial reporting of sexual dysfunction among women with either hypothyroidism or hyperthyroidism, subgroup analyses were conducted. The prevalence of sexual dysfunction was 41.8% (95% CI: 26.3–59) among women with hypothyroidism and 59.6% (95% CI: 50.5–68.1) among those with hyperthyroidism. Conclusion The notable prevalence of sexual dysfunction in women with thyroid disorders highlights the for increased awareness among this population. Targeted awareness initiatives may help mitigate the occurrence of sexual dysfunction and its adverse effects, improving overall quality of life for affected women. Clinical trial number Not applicable.